Excessive Early Gestational Weight Gain And Risk of Gestational Diabetes Mellitus in Nulliparous Women - Carreno, Carlos A. (2012)
OBJECTIVE: To estimate whether there is an association between excessive early gestational weight gain and the development of gestational diabetes mellitus (GDM) and excessive fetal growth. METHODS: This is a secondary analysis of a randomized controlled trial of vitamins C and E in nulliparous low-risk women. Maternal weight gain from prepregnancy (self-reported) to 15–18 weeks of gestation was measured, and expected gestational weight gain was determined using the Institute of Medicine (IOM) 2009 guidelines for each prepregnancy body mass index (BMI) category. Excessive early gestational weight gain was defined as gestational weight gain greater than the upper range of the IOM guidelines. Rates of GDM, birth weight greater than 4000g, and large for gestational age ([LGA], birth weight 90(th) percentile or higher) were calculated and compared between women with excessive early gestational weight gain and early nonexcessive gestational weight gain (within or below IOM guidelines). RESULTS: A total of 7,985 women were studied. Excessive early gestational weight gain occurred in 47.5% of women. Ninety-three percent of women with excessive early gestational weight gain had total gestational weight gain greater than IOM guidelines. In contrast, only 55% of women with nonexcessive early gestational weight gain had total gestational weight gain greater than IOM guidelines (p<0.001). Rates of GDM, LGA, and birth weight greater than 4000 grams were higher in women with excessive early gestational weight gain. CONCLUSIONS: In our population, excessive early gestational weight gain occurred in 93% of women who had total gestational weight gain greater than the IOM guidelines. In low-risk nulliparous women, excessive early gestational weight gain is associated with the development of GDM and excessive fetal growth.